2009
DOI: 10.3109/08860220903125306
|View full text |Cite
|
Sign up to set email alerts
|

Acute Renal Failure Associated with Acute Non-fulminant Hepatitis A: A Case Report and Review of Literature

Abstract: Most of the cases of non-fulminant hepatitis A carry good renal and overall prognosis. Here we present a case of acute renal failure associated with acute non-fulminant hepatitis A, for which kidney biopsy showed interstitial nephritis and tubular necrosis. We also review the literature and possible pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Acute kidney injury can occur in patients with HAV infection with and without ALF 4042 . Mechanisms whereby renal dysfunction may occur during acute HAV infection include hypovolemia, tubular toxicity induced by hyperbilirubinemia and immune-complex mediated nephritis 41–43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury can occur in patients with HAV infection with and without ALF 4042 . Mechanisms whereby renal dysfunction may occur during acute HAV infection include hypovolemia, tubular toxicity induced by hyperbilirubinemia and immune-complex mediated nephritis 41–43 .…”
Section: Discussionmentioning
confidence: 99%
“…The management is usually supportive although there have been reports of improvement of renal function after hemodialysis, plasmapheresis and corticosteroid use 41, 43–46 . The majority of patients recover a normal renal function although permanent renal insufficiency has been reported 40, 46 . We found that 3% of patients with HAV- induced ALF required simultaneous liver-kidney transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Although liver diseases cause irreversible renal dysfunction, such as hepatitis C virus-induced cryoglobulinemia, membranoproliferative glomerulonephritis, HRS causes reversible renal failure [ 8 , 9 ]. HRS is difficult to clinically distinguish from primary renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury can occur in patients with HAV infection with and without ALF [40][41][42] . Mechanisms whereby renal dysfunction may occur during acute HAV infection include hypovolemia, tubular toxicity induced by hyperbilirubinemia and immune-complex mediated nephritis [41][42][43] .…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%
“…The management is usually supportive although there have been reports of improvement of renal function after hemodialysis, plasmapheresis and corticosteroid use 41,[43][44][45][46] . The majority of patients recover a normal renal function although permanent renal insufficiency has been reported 40,46 . We found that 3% of patients with HAV-induced ALF required simultaneous liver-kidney transplantation.…”
Section: Author Manuscript Author Manuscriptmentioning
confidence: 99%